Micro, Small, and Medium Enterprises Sector in India: Present ;:enario and Challenges - Ali, Dr; Kumar, k (Gyan Management Journal, 2016)
Micro, Small, and Medium Enterprises [MSME) sector is : =· -=d to be one of the most crucial sectors of the Indian economy. This sector plays a vital role in _-growth of India by the way of contributing significantly to the GDP Gross Domestic Product),- - ·: _–:-.1ring output, employment generation and promotion of exports of the country. This sector -_